Coronary Artery Bypass Graft Surgery and Dementia Risk in the Cardiovascular Health Study. (April 2017) - Kuźma, Elżbieta; Airdrie, Jac; Littlejohns, Thomas J.; Lourida, Ilianna; Thompson-Coon, Jo; Lang, Iain A.; Scrobotovici, Monica; Thacker, Evan L.; Fitzpatrick, Annette; Kuller, Lewis H.; Lopez, Oscar L.; Longstreth, William T.; et al.
Abstract : Introduction: The association between history of coronary artery bypass graft surgery (CABG) and dementia risk remains unclear. Methods: We conducted a prospective cohort analysis using data on 3155 elderly adults free from prevalent dementia from the US population-based Cardiovascular Health Study (CHS) with adjudicated incident all-cause dementia, Alzheimer disease (AD), vascular dementia (VaD), and mixed dementia. Results: In the CHS, the hazard ratio (HR) for all-cause dementia was 1.93 [95% confidence interval (CI), 1.36-2.74] for those with CABG history compared with those with no CABG history after adjustment for potential confounders. Similar HRs were observed for AD (HR=1.71; 95% CI, 0.98-2.98), VaD (HR=1.42; 95% CI, 0.56-3.65), and mixed dementia (HR=2.73; 95% CI, 1.55-4.80). The same pattern of results was observed when these CHS findings were pooled with a prior prospective study, the pooled HRs were 1.96 (95% CI, 1.42-2.69) for all-cause dementia, 1.71 (95% CI, 1.04-2.79) for AD and 2.20 (95% CI, 0.78-6.19) for VaD. Discussion: Our results suggest CABG history is associated with long-term dementia risk. Further investigation is warranted to examine the causal mechanisms which may explain this relationship or whether the association reflects differences in coronary artery disease severity. Abstract : Supplemental Digital Content is available in the text.